Significance of cervical length and cervical gland area in cervical maturation - Savitha, Channaveeregowda; Jnanashree Arpitha, Venkatesh; Nagarathnamma, Rangaiah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The traditional method of predicting whether an induced labor will result in successful vaginal delivery is based on pre-induction favorability of cervix as assessed by bishop score. Currently assessment of cervical maturation by sonographically at term in induction of labor is most accurate and highly reproducible compared to Bishop score. Shortening of cervix and non-detection of cervical gland area (CGA) could correspond to cervical maturation. Methods: This study was carried out in a tertiary care teaching institute in Karnataka. 180 pregnant women at or beyond 37weeks who were planned for induction, Bishop score assessment of cervix and cervical assessment by ultrasound such as cervical length (CL) and cervical gland area was done one day prior to induction. Induction was with 0.5 mg PGE2gel. Maximum 3 inductions were carried out over a period of 24hrs. Primary outcome of the study was the onset of active labor. Results: Amongst 160 pregnant women who were induced (20 women were excluded has they underwent LSCS for some other reasons during latent phase) cervical length by sonography < 2 cm were 14 none had failed induction. Cervical gland area < 2 mm (35) and absent (30) none had failed induction. Amongst the 180 pregnant women who were induced CGA was absent in 42 all had Bishop score > 4. Cervical length < 2 cm in 14 all had Bishop score > 4. Conclusions: Sonographically detected cervical gland area and cervical length was evaluated in predicting response to induction. Absent CGA and CL < 2cm was associated with greater incidence of successful labor induction. This results show the CL and CGA has significant role in predicting outcome of labor.